2007
DOI: 10.1021/la063563i
|View full text |Cite
|
Sign up to set email alerts
|

Activity Study of Self-Assembled Proteins on Nanoscale Diblock Copolymer Templates

Abstract: Novel methods for affixing functional proteins on surfaces with high areal density have the potential to promote basic biological research as well as various bioarray applications. The use of polymeric templates under carefully balanced thermodynamic conditions enables spontaneous, self-assembled protein immobilization on surfaces with spatial control on the nanometer scale. To assess the full potential of such nanometer-scale protein platforms in biosensing applications, we report for the first time the biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 43 publications
5
65
1
Order By: Relevance
“…As presented in numerous studies, various proteins exhibit biased adsorption to one of the polymeric nanodomains (Figure 7a). [124][125][126][127] For instance, fibrinogen, horseradish peroxidase, or albumin, was found to selectively adsorb onto the PS nanodomains of the diblock copolymer surfaces (Figure 7b). [41] Furthermore, as shown in Figure 7c, protein adsorption is highly favored on the PS region close to the chemical interface defined by the two neighboring PS and PMMA nanodomains.…”
Section: Protein Adsorption On Nanostructured Block Copolymer Surfacesmentioning
confidence: 99%
“…As presented in numerous studies, various proteins exhibit biased adsorption to one of the polymeric nanodomains (Figure 7a). [124][125][126][127] For instance, fibrinogen, horseradish peroxidase, or albumin, was found to selectively adsorb onto the PS nanodomains of the diblock copolymer surfaces (Figure 7b). [41] Furthermore, as shown in Figure 7c, protein adsorption is highly favored on the PS region close to the chemical interface defined by the two neighboring PS and PMMA nanodomains.…”
Section: Protein Adsorption On Nanostructured Block Copolymer Surfacesmentioning
confidence: 99%
“…20 (However, there are a variety of physical and chemical factors that can influence protein adsorption beyond the hydrophilicity of the substrate.) In previously-reported work, the successful use of a hydrophobic-hydrophilic diblock copolymer system to pattern proteins employed a very low protein concentration of 4-20 µg/ml and a very short protein adsorption time of 20-60 s. [16][17][18][19] We are not aware of any reports of the formation of protein patterns at higher protein concentrations or for longer adsorption times using the copolymer templating method. In this work, a diblock copolymer with two hydrophobic components was explored to nanopattern proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al reported that in a polystyrene (PS)-polymethyl methacrylate (PMMA) block copolymer, surface proteins such as IgG and protein G will preferentially absorb to the PS block [120]. Further work demonstrated that spatially arranged proteins could retain their catalytic activity [121]. Utilizing the PS-b-PMMA system, a variety of proteins including horseradish peroxidase, mushroom tyrosinase, and enhanced green fluorescent protein were patterned on the block copolymer surfaces.…”
Section: Block Copolymers and Protein Patterningmentioning
confidence: 99%